Guadalajara en el primer tercio del siglo XX : economía y sociedad / Luis Enrique Esteban Barahona; prólogo de Manuel Requena Gallego - Requena Gallego, Manuel; Esteban Barahona, Luis Enrique (Biblioteca aįl ; 25)
Bibliografía : p. 229-236. Fuentes